New economic trends and the presumption rule of concluding an employment contract - Gersdorf, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The paper in question refers to different bases for employment. The author is convinced that innovativeness of economy requires an increase in the share of task-based employment and civil law relations are better suited for this. In this context the author opposes the concept of presumption of an employment contract conclusion.